Sensibilità etica e orientamento costituzionale. Note critiche alla sentenza della Corte costituzionale n. 84 del 2016 (TEST BioLaw Journal - Rivista di BioDiritto, 2016)
The article presents and criticizes the ruling n. 84/2016 of the Italian Con-stitutional Court on the research on “left over” human embryos. In particular, the au-thor focuses on the risk that the approach of the Court will lead “ethically sensitive” issues outside the scope of judicial review of legislation.
Keywords: Biolaw; Embryo research; Human dignity; Judicial review of legislation; Human embryo experimentation.